Development and trends of intergroup contact studies - Yao, Shujing; Mohd Khir, Azlina; Ma’rof, Aini Azeqa; Wan Jaafar, Wan Munira (Human Resource Management Academic Research Society, 2022)
Intergroup contact is considered as an effective intervention strategy to reduce intergroup bias, increase intergroup trust, and promote inter-group relationships. The study used CiteSpace software to do a visual analysis on the 2966 articles from the Web of Science Core Collection database between 2012 and 2022. It was found that during this period, the number of articles focus on intergroup contact increased steadily year by year, with social psychology as the main discipline background, the researchers are mainly conducted in the United States and the research content focused on intergroup contact theory, intergroup attitude, intergroup anxiety, reducing bias and other topics. Moreover, it formed the foundation of knowledge including direct contact and indirect contact, mechanism of how intergroup contact to improve intergroup bias, and intergroup contact intervention strategies. Research trends mainly include positive contact, negative contact, and social change research.